2017
DOI: 10.1093/ons/opx191
|View full text |Cite
|
Sign up to set email alerts
|

Does the Thermal Damage Estimate Correlate With the Magnetic Resonance Imaging Predicted Ablation Size After Laser Interstitial Thermal Therapy?

Abstract: The TDE is an accurate and reliable measure of ablated area in LITT in human cases as assessed on postoperative MRI. Future studies should be larger and assess reliability of the TDE when multiple lasers and planes are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…17 This conclusion was further supported in a study that evaluated whether the TDE correlates with ablative area seen on postoperative MRI in perfused intracranial pathologies, once again finding that the TDE is in fact an accurate and reliable measure of ablative area. 23 Based on these studies, we can be confident that the findings reported within this study are based on consistent and reliable data.…”
Section: Discussionsupporting
confidence: 62%
“…17 This conclusion was further supported in a study that evaluated whether the TDE correlates with ablative area seen on postoperative MRI in perfused intracranial pathologies, once again finding that the TDE is in fact an accurate and reliable measure of ablative area. 23 Based on these studies, we can be confident that the findings reported within this study are based on consistent and reliable data.…”
Section: Discussionsupporting
confidence: 62%
“…The mean energy used for ablation was 2.59 kJ for tubers and 1.70 kJ for FCD. Limited reports have sought to elucidate the thermodynamics of brain tissue in response to the varied energy of ablation, 26,28,29,35 but there is no normative data on the required amount of energy to ablate tissues, so surgeons must instead rely on the thermal damage estimate (TDE) on the Visualase workstation. 8,17,23 Our ablation procedures averaged 222.75 minutes (range 179-252 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, structures with internal flow, such as vascular and CSF spaces, act as heat sinks and enable focal ablation without damage to adjacent normal brain tissue [4][5][6]. The validity of the Arrhenius model as a reliable predictor of the ablation zone has been established in several studies [7][8][9]. However, the tissue response to ablation can be variable, particularly in heterogenous structures [10,11].…”
Section: Introductionmentioning
confidence: 99%